Changes in developmental-behavioral pediatric referral trends from a non-western country during the COVID-19 pandemic - Ömercioğlu, Emel; Yeşil, Ayşe Mete; Avcı, Hanife; Özmert, Elif N. (The Turkish Journal of Pediatrics, 2025)
Background. The global spread of coronavirus disease 2019 (COVID-19) and associated policies have caused negative consequences at the level of children, families, and services, resulting in physical, mental, and developmental issues in children, as well as limited access to healthcare. We evaluated the referral numbers, sources, and trends of a developmental-behavioral pediatrics (DBP) department in Türkiye as a Eurasian country, as well as the effects of the COVID-19 pandemic on referral variables. Methods. This retrospective cohort study examined patient referral data to the Division of Developmental Behavioral Pediatrics, Department of Pediatrics, Hacettepe University between the years 2014 and 2021. We analyzed the changes in the number of referrals over time in 3-month intervals using polynomial regression models. The impact of the COVID-19 pandemic on referral reasons was evaluated. Results. Polynomial regression analyses demonstrated significant nonlinear trends in consultation volumes across all categories. During the pre-pandemic period, referrals showed a marked increase, reaching a peak around 2018 before declining. In the post-pandemic period, an initial surge in consultations was followed by a notable decline after 2021. Notably, referral numbers had dropped to their lowest levels during the pandemic. Similarly, referrals to neonatal and pediatric clinics increased sharply until 2020, after which a plateau or slight decrease was observed, indicating a deceleration in growth over time. Referrals for perinatal-neonatal risks were 1.359 (95% confidence interval: 1.269-1.456) times higher than in the pre-pandemic period, and those for suspected autism were 1.209 (95% confidence interval: 0.987-1.478) times higher. Conclusions. Although it is encouraging that our referral trends have improved in the 1.5 years since the COVID-19 pandemic, it is thought that health service constraints caused a considerable increase in prenatal risk and suspicion of autism referrals following the pandemic. Improvement and innovation in healthcare systems to prevent the long-term detrimental impacts of periodic interruptions in healthcare on children’s development and behavior is needed.